KRAS and NRAS Testing in Metastatic Colorectal Cancer in Central Iran (Tehran): A Review on Literature of the Middle East - Shahriari-Ahmadi, Ali; Ansarinejad, Nafise; Fardad, Farshid; Abbaszadeh, Mehrdad; Sadeghi, Masoud (Indian Journal of Medical and Paediatric Oncology, 2018)
Context: The incidence of colorectal cancer (CRC) in the past three decades in Iran has made it as a major public health burden. Aims: The aim of this study is to report the prevalence of KRAS and NRAS mutations in Iran and the correlation between KRAS mutation status with clinicopathological factors and survival.Materials and Methods: In a cross-sectional study, 144 patients were entered into the study based on the criteria. Age, sex, tumor site, grade, metastasis location, familial history, KRAS/NRAS status, and survival were checked for all patients, and the patients were followed for 1 year. DNA was extracted with FFPE QIAGEN kit and then polymerase chain reaction for amplification of gene segments of KRAS and NRAS genes. Results: The mean age at diagnosis was 52.9 years (range: 27–72 years) that 39.6% patients had age <50 years and 54.2% were men. KRAS mutation was significantly more in the patients with age ≥50 compared with KRAS wild type. Furthermore, the 6-month overall survival rate in KRAS mutation patients was significantly more than KRAS wild-type patients. Liver metastasis (72.9%) had the highest prevalence of metastasis in the patients, and Grade II with 64.6% had the most prevalence. Conclusions: The metastatic CRC was more prevalent in men than women, and the mean age varied around 50–60 years. The results showed that the present study had the highest prevalence of KRAS mutation in the Middle East and Pakistan with the lowest prevalence in CRC patients.
Keywords: Colorectal cancer; Iran; KRAS; NRAS